The Relationship of Self-Concept and Learning Style with Mathematics Learning Outcomes of Students of Class VII MTSN 2 of Palangka Raya - Muhammad Hamdani; Orbit Thomas; Simpun Simpun; Rosha Safrina (BIRCU, 2022)
The aims of knowing: 1) The relationship between self-concept and mathematics learning outcomes of grade VII MTsN 2 Palangka Raya students based on visual learning styles. 2) The relationship between self-concept and mathematics learning outcomes for grade VII MTsN 2 Palangka Raya students based on auditory learning styles. 3) The relationship between self-concept and mathematics learning outcomes for grade VII students of MTsN 2 Palangka Raya City based on kinesthetic learning styles. This study uses a quantitative approach to the type of correlational research. This research was conducted in the odd semester of the 2020/2021 academic year. Based on the results of the self-concept questionnaire test results obtained 20 valid statements with a reliability coefficient of️11 = 0.84, and for the test of mathematics learning outcomes obtained 27 valid questions with a reliability coefficient️11 = 0.87. Prerequisite test results of parametric statistical analysis for normality test based on visual learning style, self-concept data obtained️2count = 31.99 > 9.49=️2tables and data on mathematics learning outcomes️2count = 13.07 > 11.07 =️2table with dk = i – 3 = 8 – 3 = 5 and a significant level of 5% which means that all data are not normally distributed. For the normality test based on the auditory learning style, self-concept data were obtained️2count = 9.21 > 7.81=️2tables and data on mathematics learning outcomes️2count = 2.76 < 7.81 =️2table with dk = i – 3 = 6 – 3 = 3 and a significant level of 5%, which means that self-concept data is not normally distributed and data on mathematics learning outcomes is normally distributed. Meanwhile, for the normality test based on kinesthetic learning styles, self-concept data were obtained️2count = 27.29 > 9.49=️2tables and data on mathematics learning outcomes️2count = 1.13 < 5.99 =️2table with dk = i – 3 = 5 – 3 = 2 and a significant level of 5%, which means that the concept data is not normally distributed and the data on mathematics learning outcomes is normally distributed. The results of the study show that: (1) there is a significant positive relationship between self-concept and students' mathematics learning outcomes based on visual learning styles, the correlation coefficient is = 0.174; (2) self-concept with students' mathematics learning outcomes based on auditory learning style, the correlation coefficient is = 0.390; (3) there is a significant positive relationship between self-concept and students' mathematics learning outcomes based on kinesthetic learning styles, the correlation coefficient is = 0.549.